Essays on Family Firm Emergence, Governance, and Performance: A Behavioral and Institutional Perspective - Ren, Zhihao (IE University, 2026)
This dissertation, Essays on Family Firm Emergence, Governance, and Performance: A Behavioral and Institutional Perspective, examines how family ownership shapes firm behavior and value creation through intertwined cognitive, behavioral, and institutional mechanisms. Building on and extending behavioral theories, it conceptualizes family ownership not merely as a structural attribute but as a dynamic system of intentions, relationships, and competences that evolve with institutional change. Anchored in China’s distinctive context of economic transition, the dissertation brings together three empirical essays to explore the emergence, governance, and performance of family firms. The first essay investigates how family owners, as competent controllers, transform privatized firms into more efficient and value-creating organizations. The second examines how transgenerational intentions arise as cognitive foundations of family firms, shaping long-term strategic behavior and investment horizons. The third explores how social-relational and legitimacy pressures condition board behavior, revealing a decoupling between structural and behavioral independence in familycontrolled firms. Collectively, these studies advance a behavioral and institutional perspective of family firms that move beyond static ownership definitions to explain how intentions, cognition, and institutional contexts jointly shape family firm behavior and outcomes. The dissertation contributes to family business research by integrating insights from ownership competence, behavioral governance, and institutional dynamics, offering a multi-level account of how family control operates across contexts of emergence, governance, and performance. It also extends the study of family firms in emerging economies by demonstrating how institutional transitions, such as privatization and demographic reforms, activate distinctive cognitive and governance mechanisms.
Ensayos sobre la formación, el gobierno y el desempeño de las empresas familiares: una perspectiva conductual e institucional
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 8 - Trabajo decente y crecimiento económico